PRIMARY AND SECONDARY SOMATIC EMBRYOGENESIS OF CACAO: THE EFFECT OF EXPLANT TYPES AND PLANT GROWTH REGULATORS - Nur Ajijah; Rr Sri Hartati (Indonesian Journal of Agricultural Science, 2019)
The success of cacao somatic embryogenesis is affected by many factors, including the basal salt medium, the genotype, the explant type, and the concentration and composition of plant growth regulators (PGRs). The study aimed to evaluate the effects of PGRs composition on the primary somatic embryo (PSE) response and the effect of explant type and PGRs composition used in inducing PSE on the secondary somatic embryogenesis (SSE) response. PSEs were induced from basal petal and staminoid explants of MCC 01 and MCC 02 clones on DKW medium containing 2,4-D 2 mg l-1 + kinetin 0.5 mg l-1 or 2,4-D 2 mg l-1 + kinetin 0.125 – 0.250 mg l-1 + thidiazuron (TDZ) 2.5 – 5 µg l-1 or 2,4-D 2 mg l-1 + TDZ 10 µg l-1. Genotype, explant type, and PGR composition dependently affected PSE response. The best PSE response was obtained from staminoid explant of MCC 02 clone on medium containing 2,4-D 2 mg l-1 + kinetin 0.5 mg l-1 (20%, 9 embryos). The explant type and PGR composition used in inducing PSEs affect the SSE response. The highest  SSE response of MCC 01 clone was obtained from petal explant with medium containing 2,4-D 2 mg l-1 + kinetin 0.5 mg l-1. The formation of SSEs could increase the multiplication rate of MCC 01 clone by 7 times.